2018
DOI: 10.4269/ajtmh.17-0824
|View full text |Cite
|
Sign up to set email alerts
|

Causal Beliefs Affect Treatment Practices and Preferences for Neonatal Danger Signs in Northwest Ethiopia: A Qualitative Study

Abstract: This study was conducted to explore the experiences of community members, particularly mothers, concerning their beliefs about the causes, treatment practices, and preferences for World Health Organization-defined neonatal danger signs in northwest Ethiopia. A phenomenological qualitative study was conducted in three districts of north Gondar Zone, Amhara region, Ethiopia, from March 10 to 28, 2016. Twelve focus group discussions were conducted involving 98 individuals. In-depth interviews were conducted with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
5
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 22 publications
2
5
0
Order By: Relevance
“…This local illness diagnosis makes the community members perceive that newborn illnesses have no medical treatment from health facilities, and rely on the traditional medicines rather than seeking care from health facilities; developing misconception on treatment options. These findings are consistent with the findings of studies conducted in central and southern Ethiopia, Nigeria, and Bangladesh in that community members use herbal medicine to treat newborn illnesses [23][24][25][26][27][28]. This study also found that community members perceive newborn illnesses as non-severe which resolve spontaneously within a few days.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…This local illness diagnosis makes the community members perceive that newborn illnesses have no medical treatment from health facilities, and rely on the traditional medicines rather than seeking care from health facilities; developing misconception on treatment options. These findings are consistent with the findings of studies conducted in central and southern Ethiopia, Nigeria, and Bangladesh in that community members use herbal medicine to treat newborn illnesses [23][24][25][26][27][28]. This study also found that community members perceive newborn illnesses as non-severe which resolve spontaneously within a few days.…”
Section: Discussionsupporting
confidence: 91%
“…In both beliefs, if newborns are taken out of home for seeking treatment, PNC, or other issues before their date of baptism or taken to the witch for blessing, community members believe that newborns would face sickness from evil spirits or others. This finding is similar to the finding of a study conducted in Ethiopia which showed tradition recommends newborns to stay at home for 40 days because they are vulnerable to malevolent spirits [27,31]. This also underscores the need to conduct a behavioral change communication to change the behavior of the community members towards newborn illnesses and their treatment.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…sunlight), newborn isolation from strangers until the newborn has been religiously blessed and ambiguous newborn personhood [7,14,17]. However, only three known studies assess the determinants of care for sick newborns in Amhara [6,18,19] with no known studies assessing household care seeking for neonatal PSBI in the region. Although findings are specific to the woredas sampled in this study, recommendations may be transferable by local and regional contexts.…”
Section: Introductionmentioning
confidence: 99%
“…In Ethiopia, beliefs about the danger of newborn illness vary from views about pathogens to spirituality [ 40 ]. Our findings regarding the belief that small or sick newborns can survive varied by implementation strength.…”
Section: Discussionmentioning
confidence: 99%